The Taxonomic and Functional Diversity of Leaf-Litter Dwelling Ants in the Tropical Dry Forest of the Colombian Caribbean - Jose Camargo-Vanegas; Sebastian de la Hoz-Pedraza; Hubert Sierra-Chamorro; Roberto J. Guerrero (Diversity)
There have been few advances in understanding the organization and dynamics of ants in tropical dry forests. The latter are a seriously threatened ecosystem, and ants are important indicators of diversity, disturbance, and restoration in forest ecosystems. Using diversity data and morphofunctional traits, we evaluated the spatial and temporal variation of taxonomic and functional ant groups; in addition, we explored the variation in functional traits and diversity among communities. Ants were sampled during the dry and rainy seasons using mini-Winkler bags. A total of 9 subfamilies, 57 genera, and 146 species were collected. Ant species composition and richness varied both spatially (75 to 119 species) and temporally (121 and 127 species). The fragments from N2 and N3 showed higher diversity than those from N1. The dissimilarity among all areas was moderate (50–60%), mainly attributable to species turnover processes (77%). Twenty functional groups were identified. The N3 fragments had the highest functional diversity, with lower resistance to species loss, while the N1 and N2 fragments reduced functional diversity and increased similarity among species. Our results highlight the importance of integrating a functional analysis with the taxonomic assessment of ants as an important contribution to understanding the organization and dynamics of this community of insects that inhabit the tropical dry forest.